P266 An outbreak of stenotrophomonas maltophilia pseudobacteremia in a paediatric hospital associated with contaminated citrated tube. (6th June 2017) - Erat, Tuğba; Yahşi, Aysun; Kara, Tuğçe Tural; Özdemir, Halil; Aysev, Derya; Ince, Erdal; Çiftçi, Ergin
Abstract : In this report, we describe pseudobacteremia of Stenotrophomonas maltophilia in a paediatric hospital. S. maltophilia was isolated from blood cultures of 14 patients with in 2 months. Most of the patients with positive blood culture were given treatment because of underlying diseases, but pseudobacteremia was suspected since majority of these patients have no clinical and laboratory findings of sepsis and consecutive blood cultures were negative. The collected environmental samples were negative. Upon these isolations continued, it was considered that contamination might occur from the citrated coagulation, hemogram or biochemical tubes. Then S. maltophilia with same antibiogram was isolated from the citrated coagulation tubes. Nine of the patients received levofloxacin for average 7 days due to underlying disease. Medical staff were re-educated about blood culture drawing procedure. After the education no further isolates of S. maltophilia have been encountered to date.